Characterization of polyacrylonitrile-based carbon fibers for gas adsorption process - Yusof, Norhaniza (2013)
Polyacrylonitrile (PAN) has been found to be the most suitable precursor for producing carbon fibers (CFs) for gas adsorption because of its advantages such as high thermal stability, high specific surface area and high adsorption properties. The objectives of this study were to prepare and characterize polyacrylonitrile (PAN)-based carbon fibers (CFs) prepared via solvent-free coagulation process and study the influence of heat treatment process parameters on its morphological structure and gas adsorption properties. The factors considered in this study were polymer PAN concentration (10 wt. % - 18 wt. %), effects of acrylamide (AM) addition (0 wt. % - 7 wt. %), the stabilization temperatures (200 oC – 300 oC), and also the activation temperatures (600 oC – 900 oC). The PAN precursor fibers were produced via solvent-free coagulation process. The coagulated PAN fibers were then collected and dried under stress in oven for three hours before being post-treated with KMnO4. The treated PAN fibers were then subjected to heat treatment process which involved stabilization, carbonization and activation steps up to 900 oC. The PAN fibers were characterized using scanning electron microscopy (SEM), Fourier transform infra-red (FTIR), x-ray diffraction (XRD), differential scanning calorimetry (DSC), thermogravimetry analysis (TGA), X-ray photoelectron spectroscopy (XPS), Vario elemental analyzer, tensile testing machine, and Nitrogen Adsorption at -196.15 oC. Experimental results showed that PAN fibers containing 5 wt. % AM has the best mechanical properties as compared to those fabricated from pure PAN and PAN/ AM with 2 wt. % and 7 wt. % of AM with the Young Modulus of 5.54 GPa. In addition, the PAN fibers with 5 wt. % AM exhibited superior exothermic trend with the lowest initiation stabilization temperatures. The best stabilization temperatures were found to be at 275 oC in air atmosphere with the Young Modulus of 7.50 GPa. Meanwhile 600 oC were the best moderate carbonization temperatures for preparing the activated carbon fibers (ACFs). The activated carbon fibers prepared at 900 oC (ACFs 900) showed the best adsorption properties compared to the other ACFs with 626.94 m²/g specific surface areas and the average pore diameter of ACFs 900 is in the microporous range (18.6 Å). In conclusion, the PAN based CFs for gas adsorption processes were successfully prepared via environmentally friendly solvent-free coagulation process and suitable heat treatment processes.